Late Wisconsinan Wood and Other Tree Remains in the Presumpscot Formation, Portland Maine - Hyland, Fay; Thompson, Woodrow; Stuckenrath, Jr., Robert (Atlantic Geology, 1978)
Well preserved tree remains have been discovered in glaciomarine clay of the Late Wisconsinan Pre sump scot Formation at Portland, Maine. Logs, branches, cones, and needles occurred, just above the contact between the clay and underlying gravel deposit. They were the first tree remains tc be found in the Presumpscot Formation. The radiocarbon ages of the logs vary considerably, but their true age is believed to be between 12,000 and 12,500 years. Specimens from the Portland locality are described in detail in the present study. The logs and needles have been identified as spruce, and the associated cones indicate that the species is white spruce, (Picea glauca (Moench) Voss). The concentration and degree of preservation of the remains suggest a local source - possibly the nearby hills that were above sea level in late-glacial time. The occurrence of the spruce logs in Portland also indicates that trees may have colonized southwestern coastal i-laine very soon after the retreat of Late Wisconsinan glacial ice from this area.